2017
DOI: 10.5897/ajar2016.12104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacing inorganic with organic trace minerals on growth performance, carcass characteristics and chemical composition of broiler thigh meat

Abstract: Micro minerals (Trace minerals) are required for normal growth and development in broilers. The present study was undertaken to compare the effect of replacing inorganic with organic trace minerals on growth performance, carcass characteristics and chemical composition of broiler thigh meat. A corn soybean based diet supplemented with organic trace minerals (OTM) (x) and an inorganic trace mineral (ITM) (y) was prepared. Four hundred eighty birds were stratified by weight and randomly assigned to 6 dietary tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The CP values of the meat samples of this experiment, which ranged from 21.18±0.66 to 22.1±0.6%. Furthermore, the AC and MC of the chicken breasts ranging from 1.47±0.25 to 1.73±0.21% and 73.43±0.95 to 74.47±1.14%, respectively, were similar to the study of Baloch et al (2017). The unaltered proximate contents of the treated chicken samples will add to the monetary value and consumer acceptability of the meat because of saving nutritional losses.…”
Section: Proximate Compositionsupporting
confidence: 66%
“…The CP values of the meat samples of this experiment, which ranged from 21.18±0.66 to 22.1±0.6%. Furthermore, the AC and MC of the chicken breasts ranging from 1.47±0.25 to 1.73±0.21% and 73.43±0.95 to 74.47±1.14%, respectively, were similar to the study of Baloch et al (2017). The unaltered proximate contents of the treated chicken samples will add to the monetary value and consumer acceptability of the meat because of saving nutritional losses.…”
Section: Proximate Compositionsupporting
confidence: 66%
“…The more bioavailable minerals offer greater stability and benefit from biochemical protection against the different chemical reactions that can occur when added to the diet itself, expecting a better bird performance and higher absorption and utilization of these minerals when supplemented (16) , as well as less environmental impact (13,17) . However, regardless of the form in which the micromineral element is presented, its functions are maintained, so the form of presentation interferes only with bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in poultry have shown that even low-level replacement of inorganic minerals with organic forms optimises the growth performance of broilers and laying performance of hens and reduces the pressure on the environment of the excreted minerals. In addition, the use of organic forms reduces antagonism between certain elements, such as Zn and Cu, and the mineral components from the proteinates have a higher retention rate and better bioavailability than inorganic salts (1,7,39,48).…”
mentioning
confidence: 99%